The role of transformational leadership and customer engagement towards shaping loyalty in experience-driven businesses in Cebu - Secretaria, Norberto M.; Pacubas, Christina Y.; Aranas, Amelia Girly L. (Edelweiss Applied Science and Technology, 2025)
Transformational Leadership (TL) is well established in influencing employee motivation and organizational performance, yet its impact on customer outcomes remains underexplored, especially in SMEs offering experience-based services. This study examines TL’s role in shaping Customer Engagement (CE) and Customer Loyalty (CL) among agri-tourism businesses in Cebu, Philippines. Guided by Burns’ and Bass’ TL framework, it investigates the effects of Idealized Influence (II), Inspirational Motivation (IM), Intellectual Stimulation (IS), and Individual Consideration (IC). Using structural equation modeling (SEM) with data from 360 repeat visitors, results show that IC (β = 0.479, p < 0.001) and II (β = 0.303, p = 0.002) significantly predict CE, while IM and IS do not. CE strongly predicts CL (β = 0.708, p < 0.001), confirming its mediating role. Further analysis reveals that IC and II indirectly foster loyalty through CE, while IM and IS have no mediating effects. Findings highlight that loyalty in experience-based businesses is driven by visible, relational, and personalized leadership behaviors rather than abstract vision or innovation. The study contributes to leadership and service marketing literature and provides agri-tourism entrepreneurs practical guidance on personalized attention and role modeling to build loyalty and remain competitive.